GRAS Salts as Alternative Low-Toxicity Chemicals for Postharvest Preservation of Fresh Horticultural Products - Palou, Lluís; Pérez-Gago, María B. (Springer, 2022)
Among means alternative to chemical fungicides to control postharvest decay of fresh horticultural products, low-toxicity chemicals, classified as food additives or Generally Recognized As Safe (GRAS) compounds, are of interest because of their low toxicological effects on mammals and minimal impact on the environment. These chemicals include some essential oils, plant extracts, and other natural compounds, but also synthetic inorganic or organic salts such as carbonates, sorbates, benzoates, acetates, paraben salts, silicates, etc. Major advantages of these salts are their inherent antimicrobial activity and high solubility in water. In general, research with GRAS salts initiates with the in vitro evaluation of the antimicrobial activity of aqueous solutions against target postharvest pathogens. Selected salt solutions and concentrations are then assayed in in vivo trials, first at the laboratory scale with fresh produce artificially inoculated with the pathogen and afterwards at semi-commercial or commercial scale with naturally infected produce. GRAS salts can also be used as antimicrobial ingredients of synthetic composite edible coatings, which can have an impact on both physiological and pathological factors limiting the postharvest life of fresh horticultural products. Coating formulation and selection is based on in vivo decay control ability and overall produce quality maintenance during cold storage.